Socialization of the Use of Flavoring Broth in Cuisine in Gombang Village, Sawit District, Boyolali Regency, Central Java: Sosialisasi Penggunaan Penyedap Rasa Pada Masakan di Desa Gombang, Kecamatan Sawit, Kabupaten Boyolali, Jawa Tengah - Richardo, Kelvin Matthew; Puyanda, Irvia Resti; Rini, Dwi Sukma Permadi; Maharani, Candra Tika Putri; Maulana, Ahmad Rizik; Rahmawati, Fitria Dwi; Nuraini, Vivi (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2025)
Flavoring broth is a food additive that is usually added when cooking a dish. Flavoring broth has a savory taste and can be sourced from vegetable or animal origin. In its use, sometimes there is no definite measure and sometimes the addition is too much. This socialization program aims to provide knowledge to PKK women in Gombang Village about the use of flavoring. The implementation of this activity is carried out through several stages, namely: 1) Observation; 2) Preparation of materials; 3) Socialization; and 4) Question and answer (Q&A). The results of the service showed that the high enthusiasm of the socialization participants was reflected in the many PKK women who asked questions in the Q&A session. The follow-up program of this activity is the practice of using flavoring broth which is carried out independently by PKK women based on knowledge from socialization materials.